Cryptophycin unit B analogues - Thomas Schachtsiek; Jona Voss; Maren Hamsen; Beate Neumann; Hans-Georg Stammler; Norbert Sewald (Beilstein Journal of Organic Chemistry)
Drug conjugates using toxic payloads are a promising approach for selectively combating cancer while sparing healthy tissue. The lack of highly cytotoxic and at the same time selective therapeutics against cancer is an ongoing challenge. Cryptophycins are a class of cyclic depsipeptides renowned for their high cytotoxicity in the picomolar range often combined with efficacy against multidrug-resistant tumour cell lines. However, cryptophycins failed as stand-alone drugs in cancer treatment, and their naturally occurring derivatives lack a covalent attachment handle. By making use of drug conjugates, toxic payloads such as cryptophycins can be selectively delivered to the target site. We present the synthesis of two conjugable cryptophycins with amino groups in unit B, representing potential payloads for drug conjugates particularly effective against multidrug-resistant cancers.